Inter-node communication performance of midimew connected mesh network - Hag, Ala Ahmed Yahya (Kulliyyah of Information & Communication Technology, International Islamic University Malaysia, 2016)
The speed of computers increases tremendously day by day. Those speedy computers are needed to solve the computational problems in many areas of life. However, the computers that are sequential-based have limit in terms of speed and not able to solve the new coming challenges that demand high performance. Fields such as astronomy, deep ocean analysis, biometric analysis, and cancer cells analysis are greatly required high performance system. Therefore, an alternative approach has been followed, which is parallel computing. Parallel computers provide computationally efficient techniques for the solution of large and difficult problem in a reasonable time. In the current researches, future Massively Parallel Computers (MPC) consisting millions of nodes to achieve high performance will be invisible to use the direct interconnection networks that used in current parallel computer systems, so Hierarchical Interconnection Networks (Rostampour, Momeni, & Rezazadeh) is the alternative approach. The determination topology of the interconnection network is the first critical step on MPC systems design, because the network topology affects the overall system performance. This research is working on the Inter-node communication performance of Midimew connected Mesh Network (MMN) to interconnect millions of nodes. MMN is one of the proposed HIN, consisting of multiple basic modules of 2D-mesh networks that are recursively interconnected by Midimew network to create higher-level networks. We propose the a deadlock-free routing algorithm for MMN by using virtual channels to avoid the deadlock and evaluate the performance of the network by using proposed routing algorithm under uniform traffic pattern. The finding of this research showed that the Inter-node communication Performance of MMN achieved an increase in throughput and reduced the latency of the network compared to other HINs, As a result of low diameters between nodes (Midimew) and well structure mechanism of routing (Dimension order routing). It is shown that the Inter-node communication Performance of the MMN is superior to that of its counter rival TESH network using TOPAZ simulator.